ČUDOVIŠNI SSSR I MITSKA ZEMLJA JUGOSLAVIJA (Philological Studies, 2019)
The period after the Second World War is a time when a new identity of Croatian Yugoslav literature was formed under the watchful eye of the Soviets. However, it was precisely this first post-war decade which was extremely heterogeneous – both at the institutional and at the poetic levels – because it was then that contradictory tendencies appeared. At that time literature may have depended on extratextual climate more than ever before, that is to say on the specific socio-political regulations and directives which defined its further development, setting both its content and form, trying to deprive it of autonomy in that way. In the first post-war decade, literature, like all other branches of the arts at that time, adopted and reflected two totally opposite political directives – the initial sovietization (1945-1948) and a fierce desovietization (late 1940s and early 1950s). Two important films more than any literary work of the time show the paradigm shift, namely the westernization of the culture discussed in this paper. The first film is Tajna dvorca I. B. (The Secret of the I.B. Castle, 1951) directed by Milan Katić. This is a ballet pantomime, a satire about the Cominform resolution that was not shown publicly before 2000 (for half a century it was considered lost!). In the film, the resolution of the Cominform is anthropomorphized as a girl who is brought back to life at a spiritist séance so she can start a revolution of the people against their government. She tries to seduce the working people of Yugoslavia unsuccessfully as they reject her with disdain, so she dies spurned. The other film was produced by a young group of authors gathered around Kerempuh and the Neugebauer brothers (Walter and Norbert), led by Fadil Hadžić. This is the first Croatian animated film Veliki miting (The Big Meeting), reminiscent in form of American animation in the style of Walt Disney, while the content is that of anti-Soviet political satire. In it, Judin, an anti-Yugoslav instigator executes the orders of the Soviet government and invents various hoaxes against the “monstrous country” of Yugoslavia (an ironic allusion to lies that the USSR spread about Yugoslavia in newspapers). The film was shown in 1951 at the main square in Zagreb and received a standing ovation.
Keywords: sovietization, desovietization, the resolution of the Cominform, antistalinist propaganda, Kerempuh, The Secret of the I. B. Castle, The Big Meeting